A Review of Central Bank Digital Currency: Current Status and Changing Trends - Fatih Ceylan (İzmir İktisat Dergisi)
Since the emergence of the Central Bank Digital Currency (CBDC), which digitally represents the legal currency of the country in which it is created, significant developments have been experienced in the global financial environment as a result of the changes brought about by the innovations. Although CBDCs offer various advantages, such as cost reduction, financial inclusion, and increasing the efficiency of payment systems, they may create some disadvantages, such as the risk of dysfunctionalization of the banking sector or decreasing the level of security. At this point, it is necessary to be aware of the possible risks it may create and to develop an optimum strategy in case such risks arise to establish a successful CBDC system and benefit from its advantages. In this context, the aim of this study is to analyze all aspects (emergence process, positive/negative sides, projects, use cases, and technical infrastructure to be used) of this digital currency and to make a comprehensive evaluation of CBDC applications around the world. The evaluations show that many countries are not indifferent to this new digital currency, which has a very high development potential, and continue their research intensively in order not to fall behind the steps taken in CBDC.